Spatial metabolomics and transcriptomics reveal cell type-specific dynamics in the placenta of patients with late-onset preeclampsia - Wei, Xiaowei; Li, Qian; Qin, Chuanmei; Zeng, Weihong; Liu, Yuxu; Lu, Jiawei; He, Jiuming; Chen, Cailian; Zhang, Xiaoqing; Lin, Yi (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe placenta is vital for fetal development, but its growth can become disordered in pregnancy complications, particularly at the maternal–fetal interface. Preeclampsia, a severe condition that arises after the 20th week of pregnancy, is characterized by hypertension and other complications, posing significant risks to both mother and fetus. Despite its importance, the underlying mechanisms of preeclampsia remain poorly understood. Unraveling these mechanisms is essential for improving outcomes and advancing treatment strategies.ObjectivesThis study aimed to explore the spatial heterogeneity of the placenta and investigate the pathogenesis of late-onset preeclampsia (LOPE).MethodsWe employed spatial transcriptomics (ST) and spatial metabolomics (SM) to map trophoblasts, fibroblasts, and immune cells, and analyze their transcriptomic and metabolomic profiles. A “spot-match” method was developed to integrate ST and SM data, revealing cell type-specific gene and metabolite changes during trophoblast differentiation.ResultsThe preeclamptic placenta showed increased fibroblasts and VCT proportions but a reduced SCT proportion. Complex interactions among trophoblasts, fibroblasts, and macrophages were observed in LOPE patients. Major metabolic reprogramming, particularly in glycerophospholipid and sphingolipid metabolism, was identified, potentially influencing trophoblast differentiation.ConclusionOur ST and SM data offer new insights into LOPE mechanisms, providing valuable information for its prevention and treatment.